The Bacterial Pathotype Group Which Attacks The IR 20 Group Variety - Suparyono Suparyono; Hartini Ramlan Hifni; Osamu Horino (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1982)
-